Gender differences in disorders comorbid with posttraumatic stress disorder among U.S. Sailors and Marines. Issue 3 (26th February 2022) - Walter, Kristen H.; Levine, Jordan A.; Madra, Naju J.; Beltran, Jessica L.; Glassman, Lisa H.; Thomsen, Cynthia J.
Abstract: Psychological comorbidity, the co‐occurrence of mental health disorders, is more often the rule than the exception among individuals with posttraumatic stress disorder (PTSD). Research shows that prevalence estimates for specific psychological disorders differ by gender; however, little is known about whether these patterns persist in the presence of a comorbid PTSD diagnosis. This study examined gender differences in prevalence estimates for conditions comorbid with PTSD using medical records for 523, 626 active duty U.S. Sailors and Marines who entered the military over an 8‐year period. Using chi‐square tests of independence, we detected statistically significant gender differences for specific comorbid conditions in the subsample of 9, 447 service members with a PTSD diagnosis. Women were more likely than men to have PTSD with comorbid adjustment, OR = 1.35; depressive, OR = 1.71; and generalized anxiety or other anxiety disorders, OR = 1.16, with the largest effects for eating, OR = 12.60, and personality disorders, OR = 2.97. In contrast, women were less likely than men to have a diagnosis of PTSD with comorbid alcohol use, OR = 0.69, and drug use disorders, OR = 0.72, with the largest effects for insomnia, OR = 0.42, and traumatic brain injury, OR = 0.17. No significant gender differences emerged for comorbid bipolar, obsessive–compulsive, panic/phobic, psychotic, or somatoform/dissociative disorders, p s = .029–.314. The results show gender differences in conditions comorbid with PTSD generally align with internalizing and externalizing dimensions. Differences in comorbidities with PTSD between women and men could have implications for treatment development and delivery.